Renewable energy integrated multi-terminal transmission system using wavelet based protection scheme - Savarapu Chandra Sekhar; G. Ravi Kumar; S.V.N.L Lalitha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The power plants behavior is crucial under faulted conditions and responses on protection systems. Major microgrid (MG) protection problem is the problem between the fault current in utilitygrid mode and microgrid mode. As conventional protection system doesn’t offer solution for all MG protection challenge, but it needs advanced protection strategy. Protection system must response to both the utilitygrid and MG faults. Fast response of protection is necessary as early as possible if the fault is occurs on utilitygrid and if the fault is occurs on MG, the protection scheme must seperate the small possible portion of MG to remove the fault. This work presents a typical MG protection scheme using digital relaying and satellite communication with wavelet detailed D1-coefficients of mother wavelet Bior 1.5. This research work is done for the detection, discrimination and locality of faults at distributed generators (DG’s) integration in multi-terminal transmission system. The algorithm tested under various faults with fault inception angles (FIA), fault impedances and fault distance of feeder line.